SELEX against whole-cell bacteria resulted in lipopolysaccharide binding aptamers - Yılmaz, Deniz; Muslu, Tuğdem; Parlar, Ayhan; Kurt, Hasan; Yüce, Meral (Elsevier B.V., 2022)
Nucleic acid aptamers are target-specific oligonucleotides selected from combinatorial libraries through an iterative in vitro screening process known as Systemic Evolution of Ligands by Exponential Enrichment (SELEX). In this report, the selection of bacteria differentiating ssDNA aptamer candidates from a combinatorial library through the whole-cell SELEX method was performed. The enriched SELEX pool was sequenced using Illumina Next-Generation Sequencing (NGS) technology and analyzed for the most abundant sequences using CLC Genomics Workbench. The sequencing data resulted in several oligonucleotide families from which three individual sequences were chosen per SELEX based on the copy numbers. The binding performance of the selected aptamers was assessed by flow cytometry and fluorescence spectroscopy, and the binding constants were estimated using binding saturation curves. Varying results were obtained from two independent SELEX procedures where the SELEX against the model gram-negative bacterium Escherichia coli provided more selective sequences while the SELEX library used against gram-positive bacterium Listeria monocytogenes did not evolve as expected. The sequences that emerged from E. coli SELEX were shown to bind Lipopolysaccharide residues (LPS) and inhibit LPS-induced macrophage polarization. Thus, it can be said that, performed whole-cell SELEX could be resulted as the selection of aptamers which can bind LPS and inhibit LPS induced inflammation response and thus can be candidates for the inhibition of bacterial infections. In future studies, the selected aptamer sequences could be structurally and chemically modified and exploited as potential diagnostic tools and therapeutic agents as LPS antagonists.
Keywords: Aptamer; SELEX; Next Generation Sequencing; Macrophage; LPS